Kinematics of a rigid about a fixed point - Sanh, Do; Khoa, Do Dang (Vietnam Journal of Mechanics, 2008)
This paper employs transmission matrices to investigate the motion of a rigid body about a fixed point. Formulas to calculate coordinates, velocities, and the accelerations of points on the body are presented. The method separates generalized velocities and accelerations making it particularly useful to the study of a wide range of problems in dynamics such as, for example, the calculation of the inertia matrix